O gênero resumo na escola como proposta de ensino da produção escrita para alunos do 8º ano - Vasconcelos, Daniel Ferreira (2019)
The learning of reading and writing is a basic factor for school success and social inclusion of students. Based on this fact, this work presents a theoretical and practical basis for the production of the genre summary by 8th grade students of Elementary School, from a municipal public school in Fortaleza – CE, aiming to develop the written production capacity of these students through the application of a didactic sequence, based on proposal by Dolz, Noverraz and Schneuwly (2004), as a methodological resource to verify students' performance in written texts, as well as to prove the efficiency of such procedure as a proposal for teaching textual production. For theoretical contribution, it is fundamentally based on the discursive genre approach of Bakhtin (2003) and writing as Vieira (2005). In addition, this work follows guidelines of National Curricular Parameters (1998) of Portuguese Language and National Curricular Common Base (2018), which guide the work with textual genres in the classroom. The analysis of the data allows the verification of significant progress in the texts produced after the application of the didactic sequence and proves the efficacy of such methodological procedure as a proposal of intervention for the teaching of text production in the 8th year of Elementary School. in summary, it is proposed a work with the school summary, a genre that responds to a demand linked to the learning of contents, especially in the school environment.